Cervantes´ «The divorce court judge" and Quevedo´s «The phantom husband»: comparative study of two interludes on marriage (Castilla. Estudios de Literatura, 2017)
This paper analyses the different comicality on marriage -without adultery- in two interludes: Cervantes´ The divorce court judge and Quevedo´s The phantom husband. It also examines the differences in the way of characterizing the figures, in the verbal display of witty style and in the scenic techniques. Cervantes´ short piece is more complex, thoughtful and realistic than Quevedo´s one. The phantom husband shows a more topical satire, a grotesque deformation of the types, a higher use of witty sayings and a deep atmosphere of unreality.
Keywords: Cervantes; Quevedo; hors d'oeuvres; comparative study